THE EFFECT OF TRAINING AND DEVELOPMENT ON JOB SATISFACTION, SKILL ENHANCEMENT AND MOTIVATION OF EMPLOYEES - Zubairi, M. N.; Khan, Tahsin Zaman (International Journal of Research -GRANTHAALAYAH, 2018)
This study examines the effect of training and development on job satisfaction, skill enhancement and motivation of employees in Mahindra Group, India. A total number of 150 participants from Mahindra Group, India were involved in the study. The study made use of questionnaires as research instrument. The results of the study show a significant difference in T&D among gender of workers in a way that female employees had a higher mean score on T&D compared to male colleages. Also, here was a strong positive significant correlation between skill enhancement and motivation which implies that effective skill enhancement program will give rise to high level of motivation among workers. Additionally, there was a strong positive significant relationship between T&D and Job satisfaction, between T&D and motivation and a significant relationship between T&D and skill enhancement. This study recommends that that companies and organizations training and development would effectively motivate workers, influence job satisfaction and improve skill enhancement among workers.